PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP NIAT CALON PEMILIH DI KOTA DENPASAR UNTUK MEMILIH PARTAI DEMOKRAT DALAM PEMILU LEGISLATIF TAHUN 2014 - Ida Bagus gede Surya Pradipta; Ni Wayan Sri Suprapti (Faculty of Economics and Business Udayana University, 2013)
According to the Attitude Theory from Fishbein and Ajzen, consumer intentions to buy is determined by the attitudes and subjective norms. This three variables can be applied to relationships in the political world as to determine the voter choice intent. The study aims is to clarify the relationship between attitudes and subjective norms to voter intentions in elect Partai Demokrat in 2014 legislative elections. Primary data was collected through survey of 120 voters in Denpasar. Sample was determined by purposive sampling with three criteria, respondents live and use their voting rights in Denpasar and minimal education is high school. The results showed voters had unfavorable attitudes, subjective norms and intentions were low. Attitudes and subjective norms has significant and positive effect on intention to choose, subjective norms influence is stronger than the attitude of voters. This result indicate the influence of external (social environment) is stronger than internalfactors. The results can not be generalized beyond the study area and therefore further research is advisable to do research with a broader area and larger sample sizes or add another variables besides attitude and subjective norm, as the popularity and credibility of the party cadres.